(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate the influence of coffee cultivation at different altitudes associated with the type of fruit processing on the diversity and density of the yeast population and on the chemical and sensorial quality of the final beverage. The experiment was conducted at Fazenda Segredo, in the municipality of Cristais, Minas Gerais, with samples of coffee harvested from plots of the Mundo Novo variety. After the samples were harvested, the coffee beans were separated into cherry varieties, and the beans were subjected to natural drying on a terrace and anaerobic fermentation in drums for 36 hours. The experimental design used was a randomized block design, in a 3x2 factorial scheme, with three repetitions per treatment. The yeast density was measured by means of the serial dilution technique and the diversity was given by the Shannon-Wiener index (H’). The classification of the beans followed the Technical Rules of Identity and Quality for the Classification of Raw Beneficiated Coffee and the sensorial analysis was done according to the Specialty Coffee Association (SCA) methodology, by judges certified by the Association. The coffee culture at the altitude of 845 meters associated with the process of anaerobic fermentation showed the highest rate of density and diversity of yeasts in the grain and the distinct sensory characteristics, resulting in a drink with differentiated flavor.